1982
DOI: 10.1037/0012-1649.18.5.671
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of hiding places and the transition to Stage IV performance in object permanence tasks.

Abstract: Three studies were conducted to test Bower's conjecture that infants' Stage IV object permanence difficulties can be attributed to their interpretation of occlusion as replacement. In the first study, several types of barriers (upright screen, inverted cup, upright box, cloth) were used in a standard object permanence procedure. The search results partially supported an order of difficulty predicted by Bower's explanation. The infants were consistently delayed, however, in retrieving objects from inside the up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 4 publications
(12 reference statements)
1
7
0
Order By: Relevance
“…First, there was the extra difficulty posed by the relation of containment; the child had to use the solidity principle to infer which cup the ball would be in, whereas the infants needed to infer only whether the object should be above or below the shelf. Containment may be a particularly difficult spatial relationship for children to understand (Dunst, Brooks, & Doxsey, 1982). Second, in the infant studies, the shelf was visible on either side of the occluder when the objects were dropped; in Experiment 1, the occluder completely covered the shelf.…”
Section: Discussionmentioning
confidence: 98%
“…First, there was the extra difficulty posed by the relation of containment; the child had to use the solidity principle to infer which cup the ball would be in, whereas the infants needed to infer only whether the object should be above or below the shelf. Containment may be a particularly difficult spatial relationship for children to understand (Dunst, Brooks, & Doxsey, 1982). Second, in the infant studies, the shelf was visible on either side of the occluder when the objects were dropped; in Experiment 1, the occluder completely covered the shelf.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, in 8 to 9 months-old infants, the following variables have a considerable effect upon search behaviour: delay between hiding and onset of search (Harris 1973), laboratory versus home environment (Acredolo 1979), transparent versus opaque screens (the former are more difficult) (Lockman 1984), locomotion versus manual reaching (Lockman 1984), number of hiding places (Cummins & Bjork 1983), self-movement versus object-movement (Bremner 1978a, Goldfield & Dickerson 1981, Wishart & Bower 1982, nature of landmarks provided (Acredolo & Evans 1980, Bremner 1978b, Butterworth, Jarrett & Hicks 1982, Goldfield & Dickerson 1981, Presson & Thrigh 1982, egocentric position of containers , Cummins & Bjork 1983, nature of position changes of containers , Sophian & Sage 1983, and, finally nature of containing or occluding object (Dunst, Brooks & Doxsey 1982).…”
Section: The Ablative Componentmentioning
confidence: 99%
“…Direct comparisons of conclusions based on gaze and reach responses are rare, but gaze responses seem to be somewhat more sensitive than reach responses. For example, Dunst, Brooks, and Doxsey (1982) allowed 7-month-old infants to retrieve an object they had seen hidden inside a small box. An analysis of reaching suggested a lack of knowledge, but an analysis of visual responses indicated that most infants knew tlie location of the object (i.e., they looked toward the top of, or inside of, the box).…”
mentioning
confidence: 99%